Perbandingan Deteksi Titer Antibodi Pascavaksinasi Rabies Berbasis Kolorimetri Menggunakan ELISA Reader dan Kamera Telepon Genggam - Santoso, Koekoeh; Herowati, Ulfatin Khoiriyah; Rotinsulu, Dordia Anindita; Murtini, Sri; Ridwan, Muhammad Yusuf; Hikman, Denny Widya; Zahid, Abdul; Wicaksono, Ardilasunu; Nugraha, Arifin Budiman; Afiff, Usamah; Wijaya, Agus; Arif, Ridi; et al. (Jurnal Veteriner; Vol 22 No 1 (2021), 2021)
Rabies is an infectious disease, zoonotic, caused by virus from the genus Lyssa virus and generally transmitted by the bite of rabid animal, especially rabies infected dog.  Rabies is preventable but is always fatal to humans if the central nervous system (CNS) is infected. Vaccination has been used as one of rabies prevention programmed.  A total of 83 samples were tested using an Indirect ELISA (Enzyme Linked Immunosorbent Assay) to identify post-vaccination rabies antibody titer.  Antibody titres correlated with absorbance values and standard solutions concentrations.  Absorbance value can be determined using ELISA reader and mobile phone camera. Absorbance were read at 450 nm and 620 nm as reference using ELISA reader and image from mobile phone camera using image processing software (ImageJ).  The aim of this study is to compared between ELISA reader as gold standard and mobile phone camera through validity testing such sensitivity, specificity, and accuracy.  There is no significant difference between gold standard and alternative test equipment.  The mobile phone camera has sensitivity 98,6%, specificity 88.8 % and accuracy 97,5%.  The image processing method using ELISA reader is relatively expensive and difficult to hold in laboratory with minimum funds.  Image processing method using a mobile phone camera with ImageJ application is expected to be an alternative tool to read the result of ELISA.